A prática pedagógica do professor de geografia do ensino fundamental - Pires, Lucineide Mendes (2009)
This research had the objective to analyze the pedagogical practice of Junior High School Geography teachers (6th to 9th grade), of the Public School System in the city of Morrinhos - Goiás. As specific objectives it intended to: verify if the pedagogical practice of the Geography teachers has suffered the influence of the changes occurred in the present society; know the pedagogical practice of the teachers who teach Geography and the practical problems faced in their daily lives; verify if the experience acquired throughout the professional life of the teachers has influenced their knowledge and practice; verify if the Geography teachers search for development. The underlying problem of this research is consisted of knowing the reason why in the teaching practice, differently from the academic practice, teachers do not consider a strict theoretical and methodological posture. Despite the great changes that occurred during the last decades because of political, economic and social relationships, a model of Geography teaching was established and it is reproduced since its origin up to the present. The fact that this process has been constructed historically contributed to the traditional method as a pedagogical practice being more frequent than we can imagine. In this perspective, some questions were brought up: Why did this happen? What makes a teacher change or not his/her pedagogical practice? The pedagogical practice of the Geography teacher needs transformation? In order to attend to these objectives a qualitative case study research was carried out because it was the best way to answer the initial questions and because it enabled a natural contact with the subjects of the research, as it considers their understanding of the studied phenomenon. Thus, some data collecting instruments were used such as: questionnaires, direct observation, semi-structured interview. This research revealed that the pedagogical practice of the investigated teachers oscillate between routine and improvisation which demonstrates not lack of preparation but a practice resulted from the reflection of a given context. In general, the practice of the teachers is concerned with the dealing of challenges and confrontations in the daily life of the teaching profession. In this sense, the teachers make use of a repertoire of knowledge acquired in various formal and informal educational contexts (knowledge of the professional education, discipline knowledge, curriculum knowledge, experiential or practical knowledge), that were constructed and reconstructed throughout their professional career. This knowledge had the purpose to confront, solve and accomplish various daily activities, either in the classroom or in the school. This research did not have the presumption to show only critiques and to judge the fragmented parts responsible for the mistakes encountered in the teaching of Geography, but it is hoped that it can contribute significantly to the process of discussion and redefinition aiming at the developing of the pedagogical practice of the Junior High Geography teacher. This practice should be concerned with the changes occurred in the present society as well as to promote discussions about the problems dealt in the teaching of Geography.